2022
DOI: 10.1093/ije/dyab270
|View full text |Cite
|
Sign up to set email alerts
|

Glycated haemoglobin (HbA1c) in mid-pregnancy and perinatal outcomes

Abstract: Background Maternal diabetes is a well-known risk factor for pregnancy complications. Possible links between long-term maternal blood sugar in the normal range and pregnancy complications are less well described. Methods We assayed glycated haemoglobin (HbA1c) in blood samples collected around the 18th week of pregnancy for 2937 singleton pregnancies in the Norwegian Mother, Father and Child Cohort Study (2000–09). Perinatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…For example, blood glucose levels that are elevated within the normal range have been associated with increased risk of preeclampsia and preterm delivery, even after controlling for BMI and other risk factors. 50 Pregnancy complications can also indicate the imminent onset of established CVD risk factors. A Dutch study that measured blood pressure, lipids, and fasting glucose after pregnancy found that new hypertension and diabetes developed sooner in women after hypertensive disorders of pregnancy than in women without pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, blood glucose levels that are elevated within the normal range have been associated with increased risk of preeclampsia and preterm delivery, even after controlling for BMI and other risk factors. 50 Pregnancy complications can also indicate the imminent onset of established CVD risk factors. A Dutch study that measured blood pressure, lipids, and fasting glucose after pregnancy found that new hypertension and diabetes developed sooner in women after hypertensive disorders of pregnancy than in women without pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Carlsen et al showed that, among women with no recorded diabetes, higher HbA1c levels at 18 gestational weeks were associated with an increased risk of pre-eclampsia. Pre-eclampsia increased by 20% per unit increase of HbA1c (95% CI: 5%, 37%) [ 51 ] and, within the highest quartile of HbA1c (35mmol/mol or greater), increasing HbA1c was related to shorter pregnancy durations and an increased risk of pre-eclampsia and preterm delivery. Conversely, the occurrence of macrosomia was not significantly related to whether studies used an HbA1c threshold > or <39 mmol/mol (5.7%) (OR 1.20, 95% CI 0.98–1.47 and OR 2.06, 95% CI 0.93–4.55, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Obese women and their newborns appear to have more occurrences of miscarriage, pregnancy and labor difficulties, postnatal morbidity, and short and long-term negative health effects on their M a n u s c r i p t a c c e p t e d f o r p u b l i c a t i o n 3 offspring than childbearing women of normal weight [6,7]. The traditional treatment for GDM is mostly based on maternal blood glucose levels and stringent blood glucose control along with strict monitoring is essential to avoid negative pregnancy outcomes [8,9]. Insulin resistance increases with gestational age in normal pregnancy and it is identified as a major contributor to GDM along with B-cell dysfunctions [10,11].…”
Section: Introductionmentioning
confidence: 99%